2007
DOI: 10.1007/s11199-007-9301-6
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Internalization of Expressive Traits, and Expectations of Parenting

Abstract: This study examined parental role salience, expectations and intentions, and the extent to which the internalization of gender associated traits may be related to these parenting variables within emerging adults. Childless undergraduates at a western Canadian university (N=236; 119 women) completed a self-report questionnaire. As predicted, role salience and expectations were positively correlated with intentions. Internalization of expressive/ feminine traits, but not instrumental/masculine traits, was positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
1
12
1
2
Order By: Relevance
“…Based on the results of the hierarchical regression analysis, our study found that femininity consistently and significantly predicted interest in infants and hedonic reactions to infants before the two-way interaction was entered. The results corroborate the findings of considerable research that has found that adults' internalization of femininity is positively associated with many facets of parenting, such as accessibility to children [31], expectations of parenting [10], and desire to have children [32].…”
Section: Plos Onesupporting
confidence: 87%
“…Based on the results of the hierarchical regression analysis, our study found that femininity consistently and significantly predicted interest in infants and hedonic reactions to infants before the two-way interaction was entered. The results corroborate the findings of considerable research that has found that adults' internalization of femininity is positively associated with many facets of parenting, such as accessibility to children [31], expectations of parenting [10], and desire to have children [32].…”
Section: Plos Onesupporting
confidence: 87%
“…While changes in gender traits were formally studied in US samples only, the pattern observed by Twenge in the late 1990s is clearly visible in results from recent studies conducted among young adults in different contexts. Indeed, in various cultural settings, male and female students were found not to differ or differ little in their expression of masculine traits, while female students expressed feminine traits to a greater extent than male students (in Canada, Yaremko and Lawson 2007;in Turkey, Özkan and Lajunen 2005;in Sweden, Snellman et al 2009). Finally, note that these results may be due to the participants' cohorts, but also to their educational level, as more highly educated individuals tend to express less pronounced stereotypical gender traits than less educated individuals (in Spanish employees, Calvo-Salguero et al 2008).…”
Section: Gender Traitsmentioning
confidence: 99%
“…On the other hand, agency-a stereotypically masculine trait-is a valued characteristic in Switzerland (for instance, Switzerland scores high on Hofstede's masculinity dimension; Hofstede 2001). This may explain why, as in many other countries (e.g., in Canada, Yaremko and Lawson 2007;in Turkey, Özkan and Lajunen 2005;in Sweden, Snellman et al 2009), female students living in Switzerland valued masculine traits as much as male students did, but scored higher in feminine traits (Moya et al 2005). A similar pattern was found in the present study.…”
Section: Introductionmentioning
confidence: 95%
“…The anticipation of psychological rewards emerges as the most predictive component of general parenting intentions (Lawson, 2004; Yaremko & Lawson, 2007) and willingness to consider selective abortion for DS (Lawson, 2006). Therefore, the link between interpersonal comfort in past encounters with individuals with DS and the perception of more psychological rewards associated with parenting a child with DS found within the present study may hold particular relevance for furthering the understanding of actual prenatal testing decision making.…”
Section: Discussionmentioning
confidence: 99%